Social Representation of “Hearing Loss” Among People with Hearing Loss: An Exploratory Cross-Cultural Study - Chundu, Srikanth; Manchaiah, Vinaya; Han, Woojae; Thammaiah, Spoorthi; Ratinaud, Pierre; Allen, Peter M. (Journal of the American Academy of Audiology, 2020)
Background Hearing loss can have an effect on the physical, psychosocial, and cognitive wellbeing of an individual. Despite the research on attitudes and stigma associated with hearing loss, people with hearing loss (PHL) continue to delay seeking help. Thus, it is vital to look at alternative theories which have been successfully used in disability research to better understand how PHL perceive hearing loss.Purpose The aim of the current exploratory study was to examine the social representation (SR) of “hearing loss” in PHL in India, Republic of Korea (ROK), United Kingdom (UK), and the United States (US).Research Design The study used a cross-sectional survey design.Study Sample In this study, 424 participants were recruited using a consecutive sampling method in four countries (India, Republic of Korea, United Kingdom, and United States).Data Collection and Analysis Data collection was conducted using a questionnaire. Data were analyzed using content analysis, similarities analysis, prototypical analysis, and chi-square analysis.Results The free associations of the PHL were grouped into 37 categories. The most commonly reported categories were communication difficulties, negative mental state, aging, assessment and management, causes of hearing loss, hearing ability or disability, hearing instruments, and symptoms of hearing loss. Similarities analysis and prototypical analysis highlighted two main negative categories (negative mental state and communication difficulties) which form the central elements of SR of hearing loss. PHL associated hearing loss mainly as a negative phenomenon, but with some positive and neutral aspects. Respondents from ROK reported a greater number of neutral associations compared with other countries. There were cross-cultural similarities and differences in terms of PHL's SR of hearing loss, but there were more similarities than differences.Conclusion The study provides an insight into how PHL collectively view their “hearing loss” and helps to develop our understanding of the influence of culture on the SR of “hearing loss.” The results will aid the development of culturally appropriate public education campaigns, marketing material, and appropriate rehabilitation for PHL.
Keywords: hearing loss; stigma; attitude; social representation; perception; societal norms